The Troll in Toll: Mal and Tram as bridges for TLR2 and TLR4 signaling - O'NEILL, LUKE; SHEEDY, FREDERICK (My University, 2007)
Signaling by two of the most important bacteria-sensing TLRs, TLR2 and TLR4, involves two adaptor proteins, MyD88 adaptor-like (Mal) and Toll/IL-1 receptor (TIR) domain-containing adaptor-inducing IFN-? (Trif)-related adaptor molecule (TRAM). Recently, new insights into the functioning of these two adapters have emerged. Mal is required by both TLRs to act as a bridge to recruit the adaptor MyD88, leading ultimately to NF-B activation. Similarly, TRAM acts as a bridge to recruit TRIF to the TLR4 complex, leading to activation of the transcription factor IFN regulatory factor 3. Consistent with Mal and TRAM being key points of control, recent evidence suggests that they are subject to regulation by phosphorylation. Further, a variant in Mal in humans has been found to protect against multiple infectious diseases. Finally, another TIR domain-containing adaptor, sterile and HEAT/armadillo motif protein (SARM), has been shown to act as an inhibitor of TRIF-dependent signaling. These recent discoveries add to the complexity of TLR signaling and highlight specific control mechanisms for TLR2 and TLR4 signaling.
PUBLISHED
PMID: 17449723
Keywords: Toll-like receptor ? signal transduction ? TLR adapters ? SARM ? innate immunity ? inflammation; Immunology, Inflammation & Infection; Neuroscience